Action research - Stringer, Ernest T. (Los Angeles, Calif. Sage, 2014)
"The Fourth Edition of Ernest T. Stringer's best-selling Action Research offers easy-to-follow, clear guidelines that enable novice practitioner researchers to move comfortably through a process of inquiry and applied research. Featuring real-life examples and providing effective solutions that foster understanding of research procedures in real-life contexts, the book offers a simple but highly effective model for approaching action research: Look: building a picture and gathering information ; Think: interpreting and explaining ; Act: resolving issues and problems. Using his own experience as a guide, Stringer encourages readers to grapple with the broader political and ethical challenges that frame each inquiry. The author's engaging style makes the book especially relevant to those working with children, young adults, or people in community contexts, and is particularly relevant to those dealing with issues of diversity or with marginalized and disenfranchised groups. Clear, concise, and practical, Stringer's accessible and engaging book is a must for students and professionals in educational, business, health, counseling, and social work settings."--Publisher's website.
Research in Professional and Public Life -- The Theory Behind the Practice -- Setting the Stage: Planning a Research Process -- Look: Gathering Data -- Think: Reflection and Analysis -- Act: Action Plans - Implementing Sustainable Solutions -- Strategic Planning -- Reports: Informing Stakeholders -- Action Research and the Internet.
Keywords: Human services -- Research; Action research